On the question of legal support mechanism for economic regulation of environmental protection and natural resources in the Republic of Kazakhstan. (Journal of actual problems of jurisprudence, 2016)
The article discusses theoretical views on the interpretation of the notion of financing environment, its constituent elements, studied the problem of determining concretized explanations essence of financing environmental protection and nature. The questions the study of objects and subjects of financing environmental protection and nature. Particular attention is paid to the problem of financing environmental protection and natural resources, on possible threats to theenvironment and wildlife on an international scale. Provides recommendations for further international cooperation in the protection of the environment and wildlife.
Keywords: environment; green economy; ecosystem; energy; land resources; environmental emissions